1985
DOI: 10.1161/01.hyp.7.1.125
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and hormonal responses to aerobic exercise.

Abstract: Twelve patients with essential hypertension (WHO stages I-II) were subjected to mild aerobic exercise for 10 to 20 weeks. The time course of changes in the resting blood pressure and multiple hormonal responses (plasma catecholamines, prostaglandin E, renin-angiotensin system, kallikrein-bradykinin system) were monitored. Depressor response of both systolic and diastolic pressures was seen, and after 5 weeks of exercise blood pressure stabilized at a significantly lower level. Adjustment of work load in respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
89
1
25

Year Published

1986
1986
1997
1997

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 193 publications
(126 citation statements)
references
References 7 publications
9
89
1
25
Order By: Relevance
“…Determination of the mechanism of depressor effects that occur in the exercise training has been given little attention, except for a recent report by Jennings et al 21 In our previous work, we pointed out a significant reduction in plasma catecholamine concentrations and increased plasma levels of prostaglandin E. 9 ' l0 We also reported that subjects with low renin hypertension responded better to exercise training (correlation coefficient, 0.78) 10 than did subjects with other types of hypertension. In the present study, the correlation coefficient between logarithm of the initial plasma renin activity and the change in systolic blood pressure was 0.51.…”
Section: Hemodynamic Effects and Humoral Responsesmentioning
confidence: 59%
See 3 more Smart Citations
“…Determination of the mechanism of depressor effects that occur in the exercise training has been given little attention, except for a recent report by Jennings et al 21 In our previous work, we pointed out a significant reduction in plasma catecholamine concentrations and increased plasma levels of prostaglandin E. 9 ' l0 We also reported that subjects with low renin hypertension responded better to exercise training (correlation coefficient, 0.78) 10 than did subjects with other types of hypertension. In the present study, the correlation coefficient between logarithm of the initial plasma renin activity and the change in systolic blood pressure was 0.51.…”
Section: Hemodynamic Effects and Humoral Responsesmentioning
confidence: 59%
“…It may be that the number of subjects was too few, the exercise intensity too mild, and the duration of exercise too short to evidence a bradycardia. As we reported, 10 20 weeks was required to see any significant reduction in the resting heart rate by the same protocol of mild exercise training.…”
Section: Hemodynamic Effects and Humoral Responsesmentioning
confidence: 77%
See 2 more Smart Citations
“…sity can reduce resting sympathetic tone 15 leading to a reduction in BP. 16 The climb on Kilimanjaro represented an endurance exercise of moderate inten-…”
Section: Acknowledgementsmentioning
confidence: 99%